A Technical Analysis of Indonesia Stock Market (IDX) Composite Index - Derry Irahadi; Sung Suk Kim (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Does technical analysis outperform a buy-and-hold strategy? This study compares the returns of technical analysis based on four indicators (moving average, relative strength index, and moving average convergence divergence) to the returns of a buy-and-hold from January 2008 to September 2021 for the Indonesian Stock Exchange Composite Index (IDX). This study collects daily closing price data, then generates buy and sell signals for each indicator. Daily returns are sorted into buy-day returns and sell-day returns, then compared to overall buy-and-hold returns. For each indicator, four t-tests are applied to see if there is a statistically significant difference between (1) buy-day returns and buy-and-hold returns, (2) sell-day returns and buy-and-hold returns, (3) buy-day returns and sell-day returns, and (4) technical analysis returns and buy-and-hold returns. This study finds that for all the t-tests, technical analysis does not statistically significantly outperform a buy and hold strategy. This finding is consistent with the IDX being weak-form market efficient.